The Dunkin Hartley Guinea Pig Is a Model of Primary Osteoarthritis That Also Exhibits Early Onset Myofiber Remodeling That Resembles Human Musculoskeletal Aging - Musci, Robert V.; Walsh, Maureen A.; Konopka, Adam R.; Wolff, Christopher A.; Peelor, Frederick F.; Reiser, Raoul F.; Santangelo, Kelly S.; Hamilton, Karyn L. (Frontiers in Physiology, 2020)
Skeletal muscle dysfunction, articular cartilage degeneration, and bone loss occur essentially in parallel during aging. Mechanisms contributing to this systemic musculoskeletal decline remain incompletely understood, limiting progress toward developing effective therapeutics. Because the progression of human musculoskeletal aging is slow, researchers rely on rodent models to identify mechanisms and test interventions. The Dunkin Hartley guinea pig is an outbred strain that begins developing primary osteoarthritis by 4 months of age with a progression and pathology similar to aging humans. The purpose of this study was to determine if skeletal muscle remodeling during the progression of osteoarthritis in these guinea pigs resembles musculoskeletal aging in humans. We compared Dunkin Hartley guinea pigs to Strain 13 guinea pigs, which develop osteoarthritis much later in the lifespan. We measured myofiber type and size, muscle density, and long-term fractional protein synthesis rates of the gastrocnemius and soleus muscles in 5, 9, and 15-month-old guinea pigs. There was an age-related decline in skeletal muscle density, a greater proportion of smaller myofibers, and a decline in type II concomitant with a rise in type I myofibers in the gastrocnemius muscles from Dunkin Hartley guinea pigs only. These changes were accompanied by age-related declines in myofibrillar and mitochondrial protein synthesis in the gastrocnemius and soleus. Collectively, these findings suggest Dunkin Hartley guinea pigs experience myofiber remodeling alongside the progression of osteoarthritis, consistent with human musculoskeletal aging. Thus, Dunkin Hartley guinea pigs may be a model to advance discovery and therapeutic development for human musculoskeletal aging.